Nucleosome acidic patch-targeting binuclear ruthenium compounds induce aberrant chromatin condensation - Gabriela E. Davey (Nature Portfolio, 2017)
Histone H2A–H2B dimers in nucleosomes contain an acidic patch, a highly electronegative cleft. Here, the authors characterize a family of binuclear ruthenium compounds that selectively target the acidic patch, generating intra-nucleosomal H2A-H2B cross-links as well as inter-nucleosomal cross-links.